Forecasting seismicity rate in the north-west Himalaya using rate and state dependent friction law. Issue 2 (15th December 2017) - Chingtham, Prasanta; Prajapati, Sanjay K.; Gahalaut, Vineet K.; Chopra, Sumer; Singha Roy, Pareshnath
ABSTRACT: In this study, rate and state Coulomb stress transfer model is adopted to forecast the seismicity rate of earthquakes ( MW ≥ 5) in the north-west Himalaya region within the testing period 2011–2013. Coulomb stress changes (ΔCFF), considered to be the most critical parameter in the model, exhibit stress increase in the whole study region, excluding the Chaman fault of the Kirthar range where significant stress shadow has been observed. The estimated background seismicity rate varies in the range 0.0–0.7 in the region, which is preoccupied by low aftershock duration of <50 years. Furthermore, a low b- value that varies between 0.54 and 0.83 is observed in Kirthar ranges, Karakoram fault and Pamir-Hindukush region. However, areas like Hazara syntaxis of the northern Pakistan and northern Pamir of the Eurasian plate exhibit higher b- values in the range 1.23–1.74. Considering constant constitutive properties of the faults (i.e. A σ = 0.05 MPa), our forecast model for variable ΔCFF and heterogeneous b- value successfully captures the observed seismicity rate of earthquakes. Results have been verified using statistical S -test. However, the model fails to capture the observed seismicity rate during the period when reconstructed for average b- value to be 0.86 and no change in ΔCFF (ΔCFF = 0).